Quantification and differentiation of egg quality as affected by hen age and storage time, with the aid of near infrared hyperspectral imaging - Badenhorst, Ruben (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.